2015
DOI: 10.3920/bm2014.0064
|View full text |Cite
|
Sign up to set email alerts
|

Plantaricin IIA-1A5 from Lactobacillus plantarum IIA-1A5 displays bactericidal activity against Staphylococcus aureus

Abstract: Plantaricin IIA-1A5 is a bacteriocin produced by Lactobacillus plantarum IIA-1A5 isolated from Indonesian beef. This research aimed to identify the genes involved in plantaricin IIA-1A5 production and examine its mode of action against Staphylococcus aureus. It has been reported that a bacteriocin structural gene, plnW, is present in genome of L. plantarum IIA-1A5. Here, we reported the presence of additional genes responsible for plantaricin precursor (plnA and plnEF) and a gene encoding the quorum sensor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 37 publications
2
38
2
2
Order By: Relevance
“…High inhibition of Gram-negative bacteria, P. aeruginosa ATCC 27853, by red dragon fruit peel extract resulted from antibacterial compounds content such as phenolic compounds. This assumption was supported by Arief et al (2015) which stated that the Gram-positive bacteria were more susceptible to antibacterial activity due to the absence of a lipoprotein wall that capable of preventing antimicrobial compounds.…”
Section: Characteristics Of Red Dragon Fruit Peel Extractssupporting
confidence: 63%
“…High inhibition of Gram-negative bacteria, P. aeruginosa ATCC 27853, by red dragon fruit peel extract resulted from antibacterial compounds content such as phenolic compounds. This assumption was supported by Arief et al (2015) which stated that the Gram-positive bacteria were more susceptible to antibacterial activity due to the absence of a lipoprotein wall that capable of preventing antimicrobial compounds.…”
Section: Characteristics Of Red Dragon Fruit Peel Extractssupporting
confidence: 63%
“…The Gram-positive bacteria are more susceptible to antibacterial activity due to the absence of a lipoprotein wall that is capable of preventing antimicrobial compounds. Red dragon fruit peel extract due to its antibacterial compounds such as phenolic compounds could inhibit the growth of bacteria [13]. Application of red dragon fruit extract on beef sausages showed that S. aureus was not detected during 20 days of cold storage.…”
Section: Red Dragon Fruit Extractmentioning
confidence: 99%
“…Plantaricin IIA-1A5 showed good characteristics as an antimicrobial [14]. Plantaricin IIA-1A5 employs bactericidal activity since it disrupts the cell membrane and promotes the release of ions, proteinaceous, and genetic materials [13]. The cell wall of Gram positive has a thicker peptidoglycan layer, which is dominantly composed of lipoteichoic acid (LTA).…”
Section: Frontiers In Staphylococcus Aureusmentioning
confidence: 99%
See 2 more Smart Citations